2012
DOI: 10.3109/10799893.2012.664552
|View full text |Cite
|
Sign up to set email alerts
|

EGFR overexpression relates to triple negative profile and poor prognosis in breast cancer patients in Tunisia

Abstract: EGFR overexpression was observed in 28.6% of Tunisian breast carcinoma, associated with unfavorable prognosis and with triple negative tumors. Systemically evaluation of EGFR in breast carcinoma could benefit especially to TN subgroup from EGFR targeting agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
16
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 39 publications
8
16
2
Order By: Relevance
“…This result is similar to those reported in other North African countries, Iraq, Sub-Saharan Africa, Korea, China, and Taiwan [18, 2432]. However, in Western countries and other Arab and Asian countries breast cancer occurs at an older age [26, 27, 3336]. The age at diagnosis represents an important prognostic factor since tumors diagnosed at younger ages are generally more aggressive and/or less responsive to treatment [3739].…”
Section: Discussionsupporting
confidence: 87%
“…This result is similar to those reported in other North African countries, Iraq, Sub-Saharan Africa, Korea, China, and Taiwan [18, 2432]. However, in Western countries and other Arab and Asian countries breast cancer occurs at an older age [26, 27, 3336]. The age at diagnosis represents an important prognostic factor since tumors diagnosed at younger ages are generally more aggressive and/or less responsive to treatment [3739].…”
Section: Discussionsupporting
confidence: 87%
“…In our previous studies, we found that a percentage of triplenegative profile was around 13 to 17% of Tunisian women [27,28]. Dent et al [29] and Tischkowitz et al [30] showing a rate of 10 to 14% of TNBC in their sample study (Table 1).…”
Section: Patient Ethnicity Of Tnbcmentioning
confidence: 85%
“…However, some recent studies have shown that the expression of this oncogenic protein varies between TNBC and non-TNBC [28,75]. In fact, in our recent study we have shown that the TNBC expresses less Bcl2 than non-TNBC and it is associated with high tumors grade and bad survival [28].…”
Section: Bcl2 Familymentioning
confidence: 96%
See 2 more Smart Citations